Integrating Shotgun Metagenomics, 16s Rrna Gene Metabarcoding and Culture Approaches: A Better Outlook for Functional Profiling of a Pah-Contaminated Soil - Festa, Sabrina (2022)
Understanding bacterial diversity and function is critical for designing bioremediation strategies. This research aimed to assess chronically hydrocarbon contaminated soil bacterial diversity and their aromatic compound degradation (ACD) potential by integrating shotgun metagenomic, 16S rRNA gene metabarcoding and culture approaches. While soil metabarcoding showed dominance of Proteobacteria, metagenomics indicated that 99,5% of the sequences were taxonomically assigned to Streptomycetales order and that almost all genes related to ACD were assigned to the latter. To inspect other phyla contribution to ACD, a functional prediction was delved, and two culture approaches were used. PICRUSt2 revealed that ACD pathways were mostly found in Alphaproteobacteria, Actinobacteria and Gammaproteobacteria classes. An enrichment culture (r-EFP) was obtained with pyrene as sole carbon and energy source and a bacterial strain (S19P6), identified as a member of Mycolicibacterium genus, was isolated. Both cultures demonstrated the ability to degrade more than 90% of the supplemented pyrene after 21 days of incubation. 16S rRNA gene metabarcoding and shotgun metagenomics approaches in r-EFP indicated predominance of Proteobacteria Phylum and the presence of genes responsible for the degradation of ACD mostly assigned to the predominant phyla. Complementing different methodologies enable the recognition of the metabolic potential of soil Proteobacteria related to ACD.